2017
DOI: 10.1016/j.redox.2017.01.016
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of cancer migration and invasion by knocking down delta-5-desaturase in COX-2 overexpressed cancer cells

Abstract: We recently reported that knockdown of delta-5-desaturase (a key enzyme that converts dihomo-γ-linolenic acid, DGLA, to the downstream ω-6 arachidonic acid) promotes formation of an anti-cancer byproduct 8-hydroxyoctanoic acid from cyclooxygenase (COX)-catalyzed DGLA peroxidation. 8-hydroxyoctanoic acid can exert its growth inhibitory effect on cancer cells (e.g. colon and pancreatic cancer) by serving as a histone deacetylase inhibitor. Since histone deacetylase inhibitors have been well-known to suppress can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 58 publications
(90 reference statements)
8
72
0
Order By: Relevance
“…Cells were washed twice with PBS, permeabilized in 0.1% Triton X-100 overnight at 4 °C. After the fixation procedure, the sections were cryoprotected in a PBS solution supplemented with 0.9 mol/l of sucrose overnight at 4 °C [ 34 ]. The primary antibodies used in the present study were as follows: caspase9 (1:1000, Cell Signaling Technology, #9504), Mff (1:1000, Cell Signaling Technology, #86668), Tom20 (1:1000, Abcam, #ab186735), HrtA2/Omi (1:1000; Abcam; #ab32092).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were washed twice with PBS, permeabilized in 0.1% Triton X-100 overnight at 4 °C. After the fixation procedure, the sections were cryoprotected in a PBS solution supplemented with 0.9 mol/l of sucrose overnight at 4 °C [ 34 ]. The primary antibodies used in the present study were as follows: caspase9 (1:1000, Cell Signaling Technology, #9504), Mff (1:1000, Cell Signaling Technology, #86668), Tom20 (1:1000, Abcam, #ab186735), HrtA2/Omi (1:1000; Abcam; #ab32092).…”
Section: Methodsmentioning
confidence: 99%
“…For example, FUNDC1, the mitochondrial outer membrane proteins, has been acknowledged as the guard of heart function in the setting of acute IR injury [66]. In addition, Bnip3, another mitochondrial receptor, exerts beneficial effects on high-fat-treated livers [67]. In the present study, we explored the role of OPA1 in renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid desaturase 1 (FADS1) is the key rate-limiting enzyme of the bioactive metabolites which convert dihomo-gamma-linolenic acid (DGLA) to AA 18 . Previous studies have shown that the expression of FADS1 was dysregulated in many cancers and that knockdown of FADS1 not only inhibited cancer growth and migration but also enhanced the cytotoxicity of chemotherapeutic agents [19][20][21][22] . However, the molecular mechanism of FADS1 in laryngeal cancer still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%